Fluororesin composition
The fluorine resin composition addresses the limitations of black coloration and flame retardancy in existing ethylene-tetrafluoroethylene copolymers by using chlorine-free additives with high muncell brightness and specific copolymer structures, achieving enhanced tensile strength, extension, and color differentiation.
Patent Information
- Application Number
- JP2021209651
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-23
- Publication Date
- 2025-02-05
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fluorine resin compositions, particularly those containing ethylene-tetrafluoroethylene copolymers, are limited by their black coloration, which impedes color differentiation in complex wiring applications, and lack sufficient flame retardancy to meet evolving environmental and regulatory demands.
A fluorine resin composition is developed that does not contain chlorine atoms, incorporating additives with high muncell brightness to enhance color differentiation and includes a copolymer with a hydroxyl group at the main chain end, along with specific ratios of tetrafluoroethylene and ethylene units, to achieve excellent flame retardancy and mechanical properties.
The composition achieves a tensile strength retention rate of 77% or more, tensile extension retention rate of 80% or more, and a muncell brightness of 5 or more, ensuring effective flame retardancy and color differentiation, making it suitable for diverse applications.
Smart Images

Figure 2025016815000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a fluororesin composition. [Background technology]
[0002] Ethylene-tetrafluoroethylene copolymers are used in many applications, such as cable sheathing, coating materials, and building structural materials, due to their high resistance to chemicals, heat, and weather. Ethylene-tetrafluoroethylene copolymers also have good flame retardancy, and are used in applications where flame retardancy is required. However, in recent years, there has been a demand for higher flame retardancy due to changes in the usage environment and amendments to related laws and regulations.
[0003] Patent Document 1 proposes a highly flame-retardant black ethylene-tetrafluoroethylene copolymer paint containing 95 to 99.5 parts by mass of an ethylene-tetrafluoroethylene copolymer, 0.5 to 5 parts by mass of a black pigment, and 5 to 20 parts by mass of a flame retardant. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] China Patent Application Publication No. 111574890 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the paint of Patent Document 1 has excellent flame retardancy but is black in color, so even if colorants other than black pigments are added, the paint will be all black and the coloring properties are poor. Such materials are not suitable for applications that require coloring properties. For example, if the cable coating material is only black, it will be very difficult to distinguish between cables in a complex wiring system. Similar problems exist with chlorine-free fluororesins other than ethylene-tetrafluoroethylene copolymers.
[0006] The present invention provides a fluororesin composition having excellent flame retardancy and colorability. [Means for solving the problem]
[0007] The present invention has the following aspects. [1] A fluororesin composition comprising a fluorine-containing resin containing no chlorine atoms and an additive that imparts flame retardancy to the fluorine-containing resin, The tensile strength is 77% or more of the tensile strength of the fluororesin, and the tensile elongation is 80% or more of the tensile elongation of the fluororesin, The additive has a Munsell color value of 5 or more; A fluororesin composition, wherein the content of the additive is 0.0001 to 20.0% by mass based on the total mass of the fluororesin composition. [2] The fluororesin composition according to [1], wherein the mass loss rate when the additive is kept in an atmosphere of 28°C and 80% RH for 14 days and then heated in an oven at 150°C for 1 hour is less than 0.3% by mass. [3] The fluororesin comprises a partially fluorinated resin, The fluororesin composition according to [1] or [2], wherein the content of the partially fluorinated resin is the highest among all the fluororesins contained in the fluororesin composition. [4] The fluororesin contains a copolymer having units based on tetrafluoroethylene and units based on ethylene, The fluororesin composition according to any one of [1] to [3] above, wherein the content of the copolymer is the highest among all the fluororesins contained in the fluororesin composition. [5] The copolymer has a hydroxyl group at a main chain end, The fluororesin composition according to [4], wherein the content of hydroxyl groups at the main chain terminals is 1 to 50%, as expressed in terms of the area ratio of the hydroxyl group peak to the overtone peak of a C—F bond in an infrared absorption spectrum. Effect of the Invention
[0008] According to the present invention, a fluororesin composition having excellent flame retardancy and colorability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The meanings and definitions of the terms used in the present invention are as follows. The "tensile strength" and "tensile elongation" are each determined by preparing a dumbbell-shaped test piece (thickness 1 mm) specified in JIS K 6251 from a sample (fluororesin composition or fluororesin) and conducting a tensile test on the test piece under conditions in accordance with JIS K 6251. "Munsell lightness" is the lightness (value) of the Munsell color system. Munsell lightness is calculated based on the X, Y, and Z values measured with a color difference meter. The "Limiting Oxygen Index" (hereinafter referred to as LOI) is an oxygen index measured in accordance with JIS K 7201-2:2007. LOI is an index of the minimum oxygen concentration (volume%) required for a sample to sustain combustion, and the higher the index, the higher the flame retardancy. "Melting point" is the temperature corresponding to the maximum of the melting peak as measured by differential scanning calorimetry (DSC). The term "melt moldable" refers to exhibiting melt flowability. The term "exhibiting melt fluidity" means that there exists a temperature at which the melt flow rate is 0.1 to 1000 g / 10 min under a load of 49 N at a temperature at least 20° C. higher than the melting point of the resin. "Melt flow rate" is the melt mass flow rate (MFR) defined in JIS K 7210:1999 (ISO 1133:1997). The term "unit based on a monomer" is a general term for an atomic group formed directly by polymerization of one monomer molecule, and an atomic group obtained by chemically converting a part of the atomic group. "Monomer" means a compound that has a polymerizable carbon-carbon double bond. The symbol "~" indicating a range of values means that the values before and after it are included as the lower and upper limits.
[0010] [Fluororesin composition] A fluororesin composition according to one embodiment of the present invention (hereinafter also referred to as the present composition) contains a fluororesin that does not contain chlorine atoms (hereinafter also referred to as fluororesin A) and an additive that imparts flame retardancy to fluororesin A (hereinafter also referred to as additive B).
[0011] <Fluororesin A> The fluororesin A may be any resin that does not contain chlorine atoms, and examples thereof include polymers having units based on at least one fluorine monomer selected from tetrafluoroethylene (hereinafter also referred to as TFE), hexafluoropropylene (hereinafter also referred to as HFP), perfluoro(alkyl vinyl ether) (hereinafter also referred to as PAVE), vinylidene fluoride (hereinafter also referred to as VdF), and vinyl fluoride.
[0012] The fluororesin A may be a homopolymer having one type of unit, or a copolymer having two or more types of units. The fluororesin may further have a unit based on a non-fluorine monomer. Examples of the non-fluorine monomer include ethylene, propylene, itaconic anhydride, vinyl acetate, etc. When the fluororesin has a unit based on a non-fluorine monomer, the unit based on the non-fluorine monomer may be of only one type or of two or more types.
[0013] As the fluororesin A, a melt-moldable fluororesin is preferred because it provides excellent moldability of the fluororesin composition. Examples of melt-moldable fluororesin include a copolymer having units based on TFE (hereinafter also referred to as TFE units) and units based on ethylene (hereinafter also referred to as E units) (hereinafter also referred to as ETFE), a copolymer having TFE units and units based on PAVE (hereinafter also referred to as PAVE units), a copolymer having TFE units and units based on HFP (hereinafter also referred to as HFP units), a copolymer having TFE units, PAVE units and HFP units, a polymer having units based on VdF, and the like. The MFR of the melt-moldable fluororesin is preferably from 0.1 to 70 g / 10 min, more preferably from 3 to 40 g / 10 min.
[0014] The melt-moldable fluororesin preferably has a melting point. The melting point of the fluororesin is preferably 160 to 325°C, more preferably 220 to 320°C, and even more preferably 250 to 270°C. When the melting point of the fluororesin is equal to or higher than the lower limit, the composition has excellent heat resistance and rigidity at high temperatures. When the melting point of the fluororesin is equal to or lower than the upper limit, the composition has excellent moldability.
[0015] The fluororesin A preferably contains a partially fluorinated resin as a main component. "Contains as a main component" means that the content is the highest among all the fluororesins A contained in the composition. A partially fluorinated resin is a fluororesin that contains hydrogen atoms, and has superior mechanical properties compared to a fully fluorinated resin that does not contain hydrogen atoms, but tends to have inferior flame retardancy. Therefore, the present invention is highly useful when the fluororesin A contains a partially fluorinated resin as a main component. The fluororesin A may further contain a fully fluorinated resin. The content of the partially fluorinated resin is preferably 50% by mass or more, more preferably 80% by mass or more, and may be 100% by mass, based on the total mass of the fluororesin A.
[0016] Examples of partially fluorinated resins include polymers having units based on a fluorine monomer containing a hydrogen atom, and polymers having units based on a fluorine monomer and units based on a non-fluorine monomer. In the partially fluorinated resin, the mass ratio of hydrogen atoms to fluorine atoms (hydrogen atoms / fluorine atoms) is preferably 10 / 90 to 2 / 98, and more preferably 5 / 95 to 3 / 97. When the hydrogen atoms / fluorine atoms ratio is equal to or more than the lower limit, the resin has excellent heat resistance, chemical resistance, and flexibility, and when it is equal to or less than the upper limit, the resin has excellent mechanical properties.
[0017] As the partially fluorinated resin, ETFE is preferred because it is excellent in moldability, electrical properties, mechanical properties, abrasion resistance, and the like. As ETFE, a copolymer having E units, TFE units, and units based on monomers other than ethylene and TFE (hereinafter also referred to as "other monomer units") is preferred, because it has even more excellent heat resistance, mechanical properties, and chemical resistance.
[0018] The other monomer may be any monomer capable of copolymerization with ethylene and TFE, and examples thereof include the compound represented by the formula 1 described below, the above-mentioned fluorine monomer (excluding TFE), and non-fluorine monomer (excluding ethylene). One type of other monomer may be used alone, or two or more types may be used in combination.
[0019] The other monomer units preferably contain a unit based on a compound represented by the following formula 1 (hereinafter also referred to as FAE) in terms of better mechanical properties and thermal stability. CH 2 =CX(CF 2 ) n Z expression 1 Here, X and Z each independently represent a hydrogen atom or a fluorine atom, and n represents an integer of 1 to 10.
[0020] X in formula 1 is preferably a hydrogen atom in that flexibility, elongation and strength are further improved. Z in formula 1 is preferably a fluorine atom in that it provides better heat resistance and chemical resistance. In formula 1, n is preferably 2 to 8, more preferably 2 to 6, and even more preferably 2, 4, or 6. When n is equal to or more than the lower limit, the mechanical properties and thermal stability of the composition are more excellent, and when n is equal to or less than the upper limit, the FAE has sufficient polymerization reactivity.
[0021] Preferred specific examples of FAE include CH 2 =CH(CF 2 ) 2 F, C.H. 2 =CH(CF 2 ) 4 F, C.H. 2 =CH(CF 2 ) 6 F, C.H. 2 =CF(CF 2) 4 F, C.H. 2 =CF(CF 2 ) 3 Among them, CH is preferred because of its excellent mechanical properties and thermal stability. 2 =CH(CF 2 ) 4 F (hereinafter also referred to as PFBE) is preferred. The FAE may be used alone or in combination of two or more kinds.
[0022] In ETFE, the molar ratio of E units to TFE units (E units / TFE units) is preferably 30 / 70 to 60 / 40, more preferably 35 / 65 to 60 / 40. When the E units / TFE units is equal to or higher than the lower limit, the melting point of ETFE is sufficiently high, and the heat resistance and rigidity at high temperatures are excellent, and when it is equal to or lower than the upper limit, the chemical resistance is excellent.
[0023] The ratio of the other monomer units is preferably 0.7 to 5.0 mol %, more preferably 0.9 to 4.0 mol %, based on the total units constituting ETFE. When the ratio of the other monomer units is equal to or higher than the lower limit, the stress crack resistance at high temperatures is further excellent, and when it is equal to or lower than the upper limit, the melting point of ETFE is sufficiently high, and the heat resistance and rigidity at high temperatures are excellent.
[0024] It is preferable that ETFE has a hydroxyl group at the main chain end. ETFE having a hydroxyl group at the main chain end tends to have a better affinity with additive B than ETFE having no hydroxyl group at the main chain end. When fluororesin A contains ETFE having a hydroxyl group at the main chain end as a main component, additive B can be well dispersed in fluororesin A, and it is easy to increase the tensile strength retention rate and tensile elongation retention rate described later. The main chain ends of ETFE can be confirmed by analyzing ETFE by infrared spectroscopy.
[0025] The content of hydroxyl groups at the ends of the main chain can be determined by the peaks of the overtones of the C-F bonds in the infrared absorption (IR) spectrum (e.g., 2210 cm -1 ) to the hydroxyl peak (e.g., 3540 cm -1The area ratio of the peak of the main chain terminal hydroxyl group is preferably 1 to 50%, and more preferably 3 to 30%. When the content of the hydroxyl group at the main chain terminal is not less than the lower limit, the dispersibility of the additive B is superior, and when it is not more than the upper limit, the heat resistance is superior. The content of hydroxyl groups at the ends of the main chain can be adjusted by the molecular weight of ETFE.
[0026] The melting point of ETFE is preferably 160 to 320° C., more preferably 245 to 270° C., and even more preferably 250 to 265° C. When the melting point of ETFE is not less than the lower limit, the heat resistance and rigidity at high temperatures are excellent, and when it is not more than the upper limit, the moldability is excellent. The melting point of ETFE can be adjusted by the molar ratio of E units to TFE units, the ratio of other monomer units to all units constituting ETFE, and the like.
[0027] The fluororesin A may be a commercially available product, or may be produced by a known production method. ETFE can be produced, for example, by the method described in paragraphs
[0021] to
[0025] of Patent Document 1 or the method described in paragraphs
[0036] to
[0043] of International Publication No. 2016 / 006644.
[0028] ETFE having a hydroxyl group at the main chain end can be obtained, for example, by using an alcohol as a chain transfer agent when polymerizing a monomer. Specifically, as described in paragraph
[0016] of JP 2016-043566 A, when an alcohol is used as a chain transfer agent, the hydroxyl group of the alcohol is introduced to the main chain end of ETFE, and ETFE having a terminal group consisting of a hydroxyl group at the main chain end is obtained.
[0029] <Additive B> Additive B has a Munsell brightness of 5 or more. The Munsell brightness of additive B is preferably 6 or more. The higher the Munsell brightness of additive B, the more preferable it is. The upper limit is not particularly limited, but is, for example, 9. Fluorine resin A is generally transparent and has excellent colorability. If additive B has a Munsell value of 5 or more, it can impart flame retardancy to fluororesin A without significantly impairing its colorability. The composition does not contain, as additive B, additives having a Munsell color value of less than 5 (for example, carbon black, titanium black).
[0030] Any additive B can be used as long as it can impart flame retardancy to fluororesin A and has a Munsell brightness of 5 or more. Additives with a Munsell brightness of 5 or more can be appropriately selected from known additives that have a flame retardancy effect (e.g., flame retardants, flame retardant auxiliaries, pigments that have a flame retardancy effect, etc.) and can be used. Examples of additive B include antimony-based flame retardants such as antimony trioxide, inorganic particles such as aluminum hydroxide, calcium hydroxide, and magnesium hydroxide, bromine-based flame retardants such as ethylene bispentabromobenzene, polybrominated diphenyl ether, polybrominated biphenyl, and tetrabromobisphenol A, and chlorine atom-containing resins. These additives may be used alone or in combination of two or more.
[0031] Examples of chlorine atom-containing resins include vinyl chloride polymers such as polyvinyl chloride and polyvinylidene chloride, polychlorotrifluoroethylene (PCTFE), and copolymers having E units and units based on chlorotrifluoroethylene (hereinafter also referred to as CTFE units) (hereinafter also referred to as ECTFE). As the chlorine atom-containing resin, ECTFE is preferred because it is compatible with the fluororesin A and is easy to increase the tensile strength retention rate and the tensile elongation retention rate. ECTFE may further contain other monomer units other than ethylene units and chlorotrifluoroethylene units. In ECTFE, the molar ratio of ethylene units / CTFE units is, for example, 30 / 70 to 70 / 30. The total content of ethylene units and CTFE units is, for example, 90 mol% or more based on the total of all units constituting ECTFE.
[0032] When Additive B is kept in an atmosphere of 28°C and 80% RH for 14 days and then heated in an oven at 150°C for 1 hour, the mass loss rate is preferably less than 0.3% by mass, more preferably less than 0.25% by mass, and even more preferably less than 0.2% by mass. The mass reduction rate is an index of the water absorption of additive B, and varies depending on the material and shape of additive B. The lower the mass reduction rate, the easier it is to blend with fluororesin A and disperse in fluororesin A. If the mass reduction rate is less than 0.3% by mass, additive B can be well dispersed in fluororesin A, and the tensile strength retention rate and tensile elongation retention rate described below are easily increased.
[0033] <Other ingredients> The present composition may further contain components other than the fluororesin A and the additive B, as necessary, to the extent that the effects of the present invention are not significantly impaired. Examples of other components include glass fiber, ceramic fiber, titanium oxide, PTFE, color master batch, phosphoric acid compound, talc, calcium carbonate, antistatic agent, lubricant, pigment, etc. These components may be used alone or in combination of two or more. From the viewpoint of colorability, the present composition preferably does not contain any component having a Munsell lightness of less than 5. Therefore, it is preferable that the other components also have a Munsell lightness of 5 or more.
[0034] <Content of each ingredient> In the present composition, the content of additive B is 0.0001 to 20.0% by mass relative to the total mass of the present composition. When the content of additive B is equal to or more than the lower limit, the composition has excellent flame retardancy, and when the content is equal to or less than the upper limit, the excellent properties of fluororesin A (chemical resistance, heat resistance, weather resistance, etc.) are fully exhibited. The content of additive B is preferably equal to or more than 0.001% by mass relative to the total mass of the present composition, more preferably equal to or more than 0.01% by mass, even more preferably equal to or more than 0.1% by mass, particularly preferably equal to or more than 1% by mass, and is preferably equal to or less than 20% by mass, more preferably equal to or less than 15% by mass.
[0035] The content of fluororesin A is 99.9999% by mass or less, preferably 99.999% by mass or less, more preferably 99.99% by mass or less, even more preferably 99.9% by mass or less, particularly preferably 99% by mass or less, and preferably 80% by mass or more, more preferably 85% by mass or more, based on the total mass of the composition. When the content of fluororesin A is equal to or more than the lower limit, the excellent properties of fluororesin A are fully exhibited, and when the content is equal to or less than the upper limit, excellent flame retardancy is achieved.
[0036] The content of other components is preferably 5% by mass or less, more preferably 3% by mass or less, relative to the total mass of the composition, and may be 0% by mass.
[0037] <Characteristics of the composition> The tensile strength of the composition is 77% or more of the tensile strength of fluororesin A. When the ratio of the tensile strength of the composition to the tensile strength of fluororesin A (hereinafter also referred to as tensile strength retention rate) is 77% or more, additive B disperses or dissolves well in fluororesin A, and additive B is likely to exhibit its flame retardant effect. In addition, durability and the like can be sufficiently ensured, resulting in excellent practicality. The tensile strength retention is preferably 80% or more. The upper limit of the tensile strength retention is not particularly limited, but is, for example, 120%. The tensile strength retention rate can be adjusted by, for example, the type, content and particle size of additive B.
[0038] The tensile strength of the composition is preferably 30 MPa or more, more preferably 35 MPa or more. If the tensile strength is equal to or more than the lower limit, the dispersibility is excellent. The upper limit is not particularly limited, but is, for example, 75 MPa, further 70 MPa, and further 65 MPa.
[0039] The tensile elongation of the composition is 80% or more of the tensile elongation of fluororesin A. When the ratio of the tensile elongation of the composition to the tensile elongation of fluororesin A (hereinafter also referred to as tensile elongation retention rate) is 80% or more, additive B disperses or dissolves well in fluororesin A, and additive B is likely to exert its flame retardant effect. In addition, durability and the like can be sufficiently ensured, resulting in excellent practicality. The tensile elongation retention is preferably 85% or more. The upper limit of the tensile elongation retention is not particularly limited, but is, for example, 120%. The tensile elongation retention rate can be adjusted by, for example, the type, content and particle size of additive B.
[0040] The tensile elongation of the present composition is preferably 200 to 700%, more preferably 300 to 650%. When the tensile elongation is equal to or higher than the lower limit, the flexibility is excellent, and when it is equal to or lower than the upper limit, the shape retention is excellent.
[0041] The Munsell brightness of the present composition is preferably 5 or more, more preferably 6 or more. If the Munsell brightness is equal to or more than the lower limit, the composition has excellent colorability. The higher the Munsell brightness of the present composition, the more preferable it is in terms of colorability. The upper limit is not particularly limited, but it is, for example, 9.
[0042] The LOI of the composition is preferably 33% or more, more preferably 35% or more. If the LOI is equal to or more than the lower limit, the composition is highly useful in applications requiring flame retardancy. The higher the LOI of the composition, the more preferable it is in terms of flame retardancy. The upper limit is not particularly limited, but is, for example, 60%.
[0043] <Method of manufacturing the present composition> The composition is produced by mixing fluororesin A and additive B so that the tensile strength retention rate and the tensile elongation retention rate are equal to or higher than the lower limit values described above. At this time, other components may be mixed, if necessary. The ratio of each of the fluororesin A, additive B, and other components to the total mass of all the raw materials to be mixed is the same as the ratio of each of the fluororesin A, additive B, and other components to the total mass of the composition.
[0044] When the fluororesin A is melt-moldable, the mixing method is preferably a method in which the fluororesin A and the additive B, and if necessary, other components, are melt-kneaded. The melt-kneading method may be a method using a known melt-kneading device. The melt kneading device may be a device having a known melt kneading function. As the melt kneading device, a single screw extruder or a twin screw extruder, which may be equipped with a screw having a high kneading effect, is preferable, a twin screw extruder is more preferable, and a twin screw extruder equipped with a screw having a high kneading effect is particularly preferable. As the screw having a high kneading effect, a screw having a sufficient kneading effect on the melt kneading object and not applying excessive shear force can be selected. From the viewpoint of the kneading effect, the L / D of the screw is preferably 20 or more, more preferably 30 to 70. "L / D" is the value obtained by dividing the total screw length L (mm) by the screw diameter D (mm). Specific examples of the melt kneading device include a Labo Plastomill kneader (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and a KZW series twin-screw kneading extruder (manufactured by Technovel Co., Ltd.).
[0045] There is no particular limitation on the method of supplying the fluororesin A and additive B to the melt kneader. The fluororesin A and additive B may be mixed in advance and supplied to the melt kneader, or the fluororesin A and additive B may be supplied separately to the melt kneader. The same applies to the other components.
[0046] The temperature when the fluororesin A and the additive B are melt-kneaded (hereinafter also referred to as the melt-kneading temperature) is preferably set depending on the fluororesin A and the additive B. The melt-kneading temperature is preferably 220 to 400°C, more preferably 250 to 350°C.
[0047] The fluororesin A and the additive B are melt-kneaded so that the tensile strength retention rate and the tensile elongation retention rate are equal to or higher than the lower limit values mentioned above. For example, by increasing the melt-kneading temperature, additive B is easily dispersed in fluororesin A, and the tensile strength retention rate and tensile elongation retention rate tend to be high. By decreasing the melt-kneading temperature, the thermal decomposition of fluororesin A is not easily promoted, and the heat resistance of the obtained composition is further improved. Increasing the extrusion shear rate makes it easier for additive B to disperse in fluororesin A, and tends to increase the tensile strength retention rate and tensile elongation retention rate. Reducing the extrusion shear rate can prevent thermal decomposition of the resin and increase the strength and elongation retention rate. Increasing the residence time of the material to be melt-kneaded in the melt-kneading device makes it easier for additive B to disperse in fluororesin A, and tends to increase the tensile strength retention rate and tensile elongation retention rate. Increasing the residence time makes it harder for thermal decomposition of fluororesin A to be promoted, and the heat resistance of the resulting composition is further improved.
[0048] <Application> The composition can be used, for example, in wire coating materials, pipe linings, semiconductor manufacturing equipment components, semiconductor structural materials, release films, packaging films, chemical transport tubes, packing, gaskets, pump linings, automobile fuel lines, tubes, blow molded containers, high frequency boards, high frequency insulating components, materials for 3D printers, architectural membrane structures, air filters, hollow fibers, and plastic screws.
[0049] <Action and effect> This composition contains additive B in a specified content, and has a tensile strength retention rate of 77% or more and a tensile elongation retention rate of 80% or more, and therefore has superior flame retardancy compared to fluororesin A. In addition, since additive B has a Munsell value of 5 or more, the composition also has a high Munsell value and excellent colorability. EXAMPLES
[0050] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the description of the following examples. Examples 1, 6 to 8, and 12 to 16 are comparative examples, and Examples 2 to 5, and 9 to 11 are working examples.
[0051] [Evaluation method] <loi> The LOI was measured in accordance with JIS K 7201-2:2007.
[0052] <Munsell value> The Munsell lightness was determined by measuring the XYZ values with a color difference meter and converting the XYZ values into Munsell hue.
[0053] <Mass reduction rate of additives> After storing the additive in an atmosphere of 28°C and 80% RH for 14 days, its mass M 1 The additive was placed in an oven at 150°C and heated for 1 hour, after which its mass M 2 The mass loss rate (g) was measured and calculated using the following formula. The smaller the mass loss rate, the lower the water absorption rate of the additive. Mass reduction rate (%)=(M 1 -M 2 ) / M 1 ×100
[0054] <Tensile properties> (Preparation of test specimens) The fluororesin composition was melt molded at 320°C to prepare a press sheet of 200 mm x 200 mm x 1 mm thickness, which was then punched out into a JIS K 6251 No. 3 dumbbell shape and left to stand for 24 hours at 23°C and 50% RH to obtain test piece A. Test piece B was obtained in the same manner as above, except that a fluororesin blended in a fluorine-containing resin composition was used instead of the fluororesin composition.
[0055] (Tensile test) For each of the obtained test pieces A and B, a tensile test was carried out using a Strograph R-2 (manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS K 6251 at 200 mm / min to determine the tensile strength (MPa) and tensile elongation (%).
[0056] (Tensile strength retention rate, tensile elongation retention rate) From the tensile strength and tensile elongation thus determined, the tensile strength retention rate and the tensile elongation retention rate were calculated according to the following formulas. Tensile strength retention rate (%) = Tensile strength of test piece A / Tensile strength of test piece B × 100 Tensile elongation retention rate (%) = Tensile elongation of test piece A / Tensile elongation of test piece B × 100
[0057] [Materials used] ETFE: ETFE obtained in Synthesis Example 1 described below. Additive B-1: Antimony trioxide, "PATOX-M" manufactured by Nippon Seiko Co., Ltd. Additive B-2: A mixture of antimony trioxide and a brominated flame retardant (ethylene bis pentabromobenzene), "FCP-1590" manufactured by Suzuhiro Chemical Co., Ltd. Additive B-3: ECTFE (SOLVEY, HALOR930LC). Additive B-4: Zinc borate, USBorax "FireBrake 500". Additive B-5: Aluminum hydroxide (boehmite), "Cerasure BMT-33" manufactured by Kawai Lime Industry Co., Ltd. Additive B-6: Silicone flame retardant, Kaneka Corporation's "Kane Ace MR-01". It should be noted that all of Additives B-1 to B-6 were white and clearly had a Munsell value of 5 or more, so the Munsell value was not measured.
[0058] [Synthesis Example 1] After degassing the inside of a 430-liter stainless steel autoclave, CF 3 (CF 2 ) 5 417.2 kg of H, 3.8 kg of methanol, and 1.9 kg of perfluorobutylethylene (hereinafter referred to as "PFBE") were charged, and the temperature was raised to 66°C while stirring, and a mixed gas of TFE / E = 83 / 17 (mol%) was introduced until the pressure reached 1.5 MPa (gauge). Next, a CF 3 (CF 2 ) 5 1048g of H solution was injected into the autoclave to start polymerization. During polymerization, a mixed gas of TFE / E=54 / 46 (mol%) and PFBE in an amount equivalent to 1.4 mol% relative to the mixed gas were continuously added so that the pressure inside the autoclave was 1.5MPa (gauge). When the amount of the mixed gas added reached 27kg, the autoclave was cooled, and a part of the residual monomer gas was purged to obtain ETFE slurry 1. 120kg of the obtained slurry 1 was stored in a storage tank, and the obtained ETFE slurry was charged into a 220L (liter) granulation tank charged with 77kg of water, and then the temperature was raised to 105°C while stirring, and the solvent was distilled off while granulating to obtain powdered ETFE dried product 1, and ETFE having a hydroxyl group at the main chain end was obtained. The copolymerization composition of the obtained ETFE was E unit / TFE unit (molar ratio) = 54.1 / 45.9, PFBE unit was 1.4 mol% relative to the total units constituting ETFE, the melting point was 259°C, and MFR was 9.8g / 10min. The mass ratio of hydrogen atoms / fluorine atoms calculated from the copolymerization composition was 4 / 96. The content of hydroxyl groups at the main chain terminals was 9% relative to the overtone peak of the CF bond in terms of the area ratio of the ETFE IR spectrum.
[0059] [Examples 1 to 16] ETFE and the additives shown in Table 1 were mixed so that the final additive contents were the values shown in Table 1, and kneaded in a twin-screw extruder to obtain a fluororesin composition. The additive content is the ratio (mass%) of the additive to the total mass of the fluororesin composition. The tensile properties, LOI, and Munsell value of the obtained fluororesin compositions were evaluated. The results are shown in Table 1. Note that, for Examples 12 to 16, the tensile strength and tensile elongation were low and the practical use was poor, so the LOI was not measured.
[0060] [Table 1]
[0061] Examples 2 to 5 and 9 to 11 had higher LOI and better flame retardancy than Example 1 consisting of only a fluororesin. In addition, the Munsell value of the entire fluororesin composition was also high, and the colorability was excellent. On the other hand, Examples 6 to 8, in which the tensile strength retention was less than 77% and the tensile elongation retention was less than 80%, were poor in flame retardancy.< / loi>
Claims
1. A fluororesin composition comprising a fluorine-free resin and an additive that imparts flame retardancy to the fluorine-free resin, The tensile strength is 77% or more of the tensile strength of the fluororesin, and the tensile elongation is 80% or more of the tensile elongation of the fluororesin, The additive has a Munsell color value of 5 or more, A fluororesin composition, characterized in that the content of the additive is 0.0001 to 20.0 mass % based on the total mass of the fluororesin composition.
2. 2. The fluororesin composition according to claim 1, wherein the additive is kept in an atmosphere of 28° C. and 80% RH for 14 days and then heated in an oven at 150° C. for 1 hour, and the mass loss rate is less than 0.3% by mass.
3. the fluororesin comprises a partially fluorinated resin, 3. The fluororesin composition according to claim 1, wherein the partially fluorinated resin has a highest content among all the fluororesins contained in the fluororesin composition.
4. the fluororesin comprises a copolymer having a unit based on tetrafluoroethylene and a unit based on ethylene, The fluororesin composition according to any one of claims 1 to 3, wherein the content of the copolymer is the highest among all the fluororesins contained in the fluororesin composition.
5. The copolymer has a hydroxyl group at a main chain end, 5. The fluororesin composition according to claim 4, wherein the content of hydroxyl groups at the main chain terminals is 1 to 50%, as expressed in terms of an area ratio of a hydroxyl group peak to a C—F bond overtone peak in an infrared absorption spectrum.
Citation Information
Patent Citations
High-flame-retardant black ethylene-tetrafluoroethylene copolymer coating and preparation method thereof
CN111574890A